(untitled) (University Journal of Zoology, Rajshahi University, 2012)
100 nematode specimens under the genus Aporcelaimellus was identified from different cultivated crops. The genus is within the family Dorylaimidae, and contains robust animals of 0.8 to 3.5 mm body length. The specimen having the medium-sized body, short odontostyle, unsclerotized vulva, conical, dorsally not concave tail with distinctly separated layers of terminal cuticle. Aporcelaimellus prevalence was the highest in banana (80%) and the lowest was in mulberry (20%) during sampling periods. The diagnostic morphology of this nematode was slender vulva lips, thick vagina, and with long anal body with sharply pointed tail. DOI: http://dx.doi.org/10.3329/ujzru.v30i0.10752 Univ. j. zool. Rajshahi Univ. Vol. 30, 2011 pp. 45-48